2014
DOI: 10.1038/srep04534
|View full text |Cite
|
Sign up to set email alerts
|

Random allocation of pies promotes the evolution of fairness in the Ultimatum Game

Abstract: In the Ultimatum Game, two players are offered a chance to win a pie. The proposer suggests how to split the pie. The responder can either accept or reject the deal. If an agreement is not reached, neither player gets anything. Both game theory and evolutionary game theory predict the rational solution that the proposer offers the smallest possible share and the responder accepts it. Fairness thus requires additional mechanisms for natural selection to favor it. Studies to date assumed that individuals have co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…This is because individuals with self-incompatible strategies obtain nothing when interacting with themselves. Consequently, they have little chance of surviving in the structured population (Wang et al, 2014). Furthermore, we notice that the most common selfcompatible strategies first move towards the right, and then the left of the concrete strategy space, as the increment of node degree k. The offer and acceptance level calculated by both computer simulations and theoretical analysis support our naked-eye observation (see Fig.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…This is because individuals with self-incompatible strategies obtain nothing when interacting with themselves. Consequently, they have little chance of surviving in the structured population (Wang et al, 2014). Furthermore, we notice that the most common selfcompatible strategies first move towards the right, and then the left of the concrete strategy space, as the increment of node degree k. The offer and acceptance level calculated by both computer simulations and theoretical analysis support our naked-eye observation (see Fig.…”
Section: Resultssupporting
confidence: 77%
“…4 can be provided as follows. In a previous study (Wang et al, 2014), we have shown that the tradeoff between rejecting unfair offers (achieving by maintaining high a) and making more successful deals (achieving by decreasing a) results in the best acceptance thresholds for individuals in structured populations. When node degree k is low, the former factor (i.e., rejecting unfair offers) is much more important than the latter one (i.e., making more successful deals), which leads to the maintenance of high acceptance level a.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It has been demonstrated that the mode of individual mobility does influence the evolutionary dynamics of cooperation among unrelated individuals, which has attracted intensive research activity in recent years [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Theoretical and experimental studies have shown that individual mobility can promote the evolution of cooperation [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. In particular, Meloniet al considered random migration for individuals playing the prisoner's dilemma game on a twodimensional plane and found that cooperation can be maintained when the moving velocity of individuals is not too high [28].…”
Section: Introductionmentioning
confidence: 99%